Beeswax crystals form a network structure in highly unsaturated oils and O/W emulsions under supersaturation and cool temperature conditions - Han, Wanjun; Chai, Xiuhang; Zaaboul, Farah; Tan, Chin-Ping; Sun, Yanwen; Liu, Chunhuan; Liu, Yuanfa (Academic Press, 2022)
Beeswax (BW) is widely used in structured oil to mimic fat crystals, due to its needle-like crystal structure and effective gelling ability. In this study, the crystallization behavior of BW in liquid oil was analyzed at different cooling temperatures and BW concentrations. Results showed that temperature and BW concentrations played a role in reaching the supersaturation state for the system of BW in linseed oil, with 40%BW at 20 °C and 20%BW at 5 °C, respectively. Short nuclear induction time and higher crystallinity of BW were found at lower cooling temperatures, promoting formation of supersaturation state. In addition, the apparent activation energy of the crystallization process indicates that crystallization is inhibited at high BW concentrations. Furthermore, higher supersaturation levels and lower cooling temperatures affected the droplet size and crystal structure of the O/W emulsions; these conditions accelerated the penetration of crystals through the interfacial membrane and led to droplet aggregation and coalescence. High supersaturation level and low cooling temperature promoted emulsion instability and had a remarkable impact on food quality.